Exploring the versatility of gingiva-colored composite - Paryag AA; Rafeek RN; Mankee MS; Lowe J (Dove Medical Press, 2016)
Amit A Paryag,1 Reisha N Rafeek,1 Melissa S Mankee,2 Jenai Lowe1 1School of Dentistry, The University of the West Indies, Mount Hope, 2Tooth Haven Dental Studio, D'Abadie, Trinidad and Tobago Abstract: Gingival recession has a diverse etiology. The consequences may include gingivitis, periodontitis, and hypersensitivity. Whereas the management can include surgical treatment options, sometimes a more conservative, yet still esthetic approach may be required. The use of gingiva-colored composites provides one such alternative and can be applied to varying presentations of the problem. While surgical treatment can be successful in re-creating favorable esthetic anatomy as well as achieving accurate tissue contour in cases when minor amounts of tissue are reconstructed, long-term results vary because of the vascularity and complexity of the interdental space. Factors such as cost, healing time, discomfort, and variable long-term results make surgery an unpopular choice. If tooth-colored restorative materials are utilized to restore cervical tooth exposure as a result of severe recession, the disproportionate appearance of the visible crown may give a dissatisfying result. Gingiva-colored composite provides dental practitioners with a versatile material that can be used to directly restore cervical defects caused by gingival recession, thus correcting the appearance of the gingival anatomy. It offers a treatment option that may increase patient satisfaction through the provision of a cost-effective, minimally invasive solution with highly esthetic results. Keywords: gingiva composite, cervical restoration, esthetics